Inclusive Education in the Current Context of Innovations of Education in Vietnam - Trang THU, Dinh Nguyen; Hung, Nguyen Van; Phuong, Nguyen Minh; Thuy, Do Thi Thanh (Angstrom Centre of Education, 2024)
This article summarizes the process of developing inclusive education policies and services in Vietnam from its initial application to the current extent. The model of inclusive education has raised access, support, participation and success for children and young people with disabilities. In 2018, Vietnam carried out an overall innovation of the general education program, leading to many changes in inclusive education for people with disabilities. Data sources include analysis of policies related to people with disabilities (e.g. Law on People with Disabilities, 2010; Circular on educational policies for people with disabilities, 2013; Circular on inclusive education for people with disabilities, 2018; Circular on support centers for inclusive education development, 2022); innovative educational programs (e.g. preschool education program, 2020; general education program, 2022); research (e.g. The research on ensuring the quality of inclusive education for children with disabilities in Vietnamese secondary and high schools, Nguyen Xuan Hai, 2016; Support center for inclusive education development – conditions for ensuring the quality of inclusive education, Le Van Tac, 2015); results of surveys, in-depth interviews, research on records on the development of inclusive teaching capacity of secondary and high school teachers. Reported impacts include public awareness raising and support for children with disabilities, development of local policies and infrastructure for inclusive education, capacity building of educators to educate children with disabilities and improve the quality of life for people with disabilities. Remarkably, the first Master's and Doctoral training programs in special education in Vietnam has been developed in Hanoi National University of Education; training program for education leaders in preparation for the enhancement of inclusive education in local communities have also been implemented across the country. In addition to that, the article examines the barriers and difficulties in implementing inclusive education in the context of renovation of education and lessons learned. On that basis, the authors propose the next steps to: 1) Strengthen consensus on the choice of inclusive education for children with disabilities in Vietnam, 2) Increase the use of effective teaching strategies for inclusive classrooms, and 3) Orientate/Strengthen to develop resources to effectively support inclusive education for children with disabilities in all over the country.